2001
DOI: 10.1149/1.1383428
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Solvation of Lithium Ions in Organic Electrolyte Solutions by Electrospray Ionization-Mass Spectroscopy

Abstract: Solvation of lithium ions in organic electrolyte solutions, ethylene carbonate ͑EC͒, propylene carbonate ͑PC͒, and ␥-butyrolactone ͑GBL͒ containing LiClO 4 , for lithium batteries was studied by electrospray ionization-mass spectroscopy ͑ESI-MS͒. The mass spectrograms showed that a lithium ion solvated with two or three solvent molecules. In the course of the research and development of advanced batteries, the selection of the electrolyte solution has been an important factor. The solvent molecules react with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 9 publications
6
57
1
1
Order By: Relevance
“…Thus, both solvated species reach equilibrium in the solution. In the ESI-MS study, it was reported that Li + (PC) 3 was observed [12][13][14]. However, there is no contradiction between the ESI-MS study and the present work.…”
Section: Single Reflection Atr Spectracontrasting
confidence: 60%
See 1 more Smart Citation
“…Thus, both solvated species reach equilibrium in the solution. In the ESI-MS study, it was reported that Li + (PC) 3 was observed [12][13][14]. However, there is no contradiction between the ESI-MS study and the present work.…”
Section: Single Reflection Atr Spectracontrasting
confidence: 60%
“…On the other hand, it is well known that when lithium ions are solvated using nonaqueous organic solvents [6][7][8][9][10][11][12][13][14], the solvents affect the reduction potential and the subsequent decomposition reactions. When considering rechargeable lithium ion batteries, it is important to understand the behavior of species solvated to lithium ions during the charging and discharging phases.…”
Section: Introductionmentioning
confidence: 99%
“…129,[169][170][171] Using a new mass spectrum (MS) technique, a more recent determination of the coordination number (CN) for lithium ions seems to support these computational results: among the various solvated lithium ion species, the peaks corresponding to Li(solv) 2∼3 + are the most abundant no matter whether the solvent is EC, PC, or γ-butyrolactone (γBL). 172,173 This latter experimental observation also revealed the stability of the solvation sheath, which obviously remains intact even during the electrospraying under vacuum and the subsequent ionization process. Therefore, there should be sufficient confidence in the general belief that the composition of solvated lithium ion remains unchanged during its migration in an electrolyte solution.…”
Section: Ion Transport Propertiesmentioning
confidence: 73%
“…When E S is cathodically polarized from 0.7 to 0.02 V, lithium ions desolvate firstly from solvated solvent molecules, and then alloy with Sn-Co anode. As a result, if taking account of solvation/desolvation reactions in the lithiation/delithiation processes [23], the Eq. (2) could be rewritten as:…”
Section: Electrochemical Studiesmentioning
confidence: 99%